Activin B antagonizes RhoA signaling to stimulate mesenchymal morphology and invasiveness of clear cell renal cell carcinomas - Wacker, Ingrid; Behrens, Jürgen (PLoS ONE, 2014)
Activin B belongs to the TGF? family of growth factors and is upregulated in clear cell renal cell carcinoma cells by hypoxia inducible factors. Expression of Activin B is required for tumor growth in vivo and tumor cell invasion in vitro. Here we show that activation of RhoA signaling counteracts Activin B mediated disassembly of actin stress fibers, mesenchymal cell morphology and invasiveness, whereas inhibition of RhoA rescues these effects in Activin B knockdown cells. Conversely, Activin B inhibits RhoA signaling suggesting that there is an antagonistic connection between both pathways. In addition we found that Rac1 plays an opposite role to RhoA, i.e. activation of Rac1 initiates loss of actin stress fibers, promotes a mesenchymal cell morphology and induces invasion in Activin B knockown cells, whereas inhibition of Rac1 abolishes these Activin B effects. Collectively, our data provide evidence that reduction of RhoA signaling by Activin B together with persistent Rac1 activity is a prerequisite for inducing an invasive phenotype in clear cell renal cell carcinoma.
EVALuna2:10307

Adenomatous polyposis coli (APC) membrane recruitment 3, a member of the APC membrane recruitment family of APC-binding proteins, is a positive regulator of Wnt-?-catenin signalling - Brauburger, Katharina; Akyildiz, Senem; Ruppert, Jan G.; Graeb, Michael; Bernkopf, Dominic; Hadjihannas, Michel; Behrens, Jürgen (Febs Journal, 2014)
The adenomatous polyposis coli (APC) membrane recruitment (Amer) family proteins Amer1/Wilms tumour gene on the X chromosome and Amer2 are binding partners of the APC tumour suppressor protein, and act as negative regulators in the Wnt signalling cascade. So far, nothing has been known about the third member of the family, Amer3. Here we show that Amer3 binds to the armadillo repeat domain of APC, similarly to Amer1 and Amer2. Amer3 also binds to the Wnt pathway regulator conductin/axin2. Furthermore, we identified Amer1 as binding partner of Amer3. Whereas Amer1 and Amer2 are linked to the plasma membrane by an N-terminal membrane localization domain, Amer3 lacks this domain. Amer3 localizes to the cytoplasm and nucleus of epithelial cells, and this is dependent on specific nuclear import and export sequences. Functionally, exogenous Amer3 enhances the expression of a ?-catenin/T-cell factor-dependent reporter gene, and knockdown of endogenous Amer3 reduces Wnt target gene expression in colorectal cancer cells. Thus, Amer3 acts as an activator of Wnt signalling, in contrast to Amer1 and Amer2, which are inhibitors, suggesting a nonredundant role of Amer proteins in the regulation of this pathway. Our data, together with those of previous studies, provide a comprehensive picture of similarities and differences within the Amer protein family.AMER3 physically interacts with APC by two hybrid (1, 2). AMER3 physically interacts with APC by anti tag coimmunoprecipitation (1, 2, 3). APC physically interacts with AMER3 by anti bait coimmunoprecipitation (View interaction). AMER3 physically interacts with APC, AMER1 and Conductin by anti bait coimmunoprecipitation (View interaction). AMER3 physically interacts with AMER1 by anti tag coimmunoprecipitation (1, 2). AMER3 and APC colocalize by fluorescence microscopy (View interaction). Conductin physically interacts with AMER3 by anti tag coimmunoprecipitation (View interaction). APC physically interacts with AMER2 by anti tag coimmunoprecipitation (View interaction). Conductin physically interacts with AMER3 by anti tag coimmunoprecipitation (1, 2). AMER1 and AMER3 colocalize by fluorescence microscopy (View interaction). APC physically interacts with AMER1 by anti tag coimmunoprecipitation (View interaction).
EVALuna2:10304

Amer2 protein interacts with EB1 protein and adenomatous polyposis coli (APC) and controls microtubule stability and cell migration. - Pfister, Astrid; Hadjihannas, Michel; Roehrig, Waldemar; Schambony, Alexandra; Behrens, Jürgen (Journal of Biological Chemistry, 2012)
EB1 is key factor in the organization of the microtubule cytoskeleton by binding to the plus-ends of microtubules and serving as a platform for a number of interacting proteins (termed +TIPs) that control microtubule dynamics. Together with its direct binding partner adenomatous polyposis coli (APC), EB1 can stabilize microtubules. Here, we show that Amer2 (APC membrane recruitment 2), a previously identified membrane-associated APC-binding protein, is a direct interaction partner of EB1 and acts as regulator of microtubule stability together with EB1. Amer2 binds to EB1 via specific (S/T)xIP motifs and recruits it to the plasma membrane. Coexpression of Amer2 and EB1 generates stabilized microtubules at the plasma membrane, whereas knockdown of Amer2 leads to destabilization of microtubules. Knockdown of Amer2, APC, or EB1 reduces cell migration, and morpholino-mediated down-regulation of Xenopus Amer2 blocks convergent extension cell movements, suggesting that the Amer2-EB1-APC complex regulates cell migration by altering microtubule stability.

Amer2 protein is a novel negative regulator of Wnt/β-catenin signaling involved in neuroectodermal patterning. - Pfister, Astrid; Tanneberger, Kristina; Schambony, Alexandra; Behrens, Jürgen (Journal of Biological Chemistry, 2012)
Wnt/β-catenin signaling is negatively controlled by the adenomatous polyposis coli (APC) tumor suppressor, which induces proteasomal degradation of β-catenin as part of the β-catenin destruction complex. Amer2 (APC membrane recruitment 2; FAM123A) is a direct interaction partner of APC, related to the tumor suppressor Amer1/WTX, but its function in Wnt signaling is not known. Here, we show that Amer2 recruits APC to the plasma membrane by binding to phosphatidylinositol 4,5-bisphosphate lipids via lysine-rich motifs and that APC links β-catenin and the destruction complex components axin and conductin to Amer2. Knockdown of Amer2 increased Wnt target gene expression and reporter activity in cell lines, and overexpression reduced reporter activity, which required membrane association of Amer2. In Xenopus embryos, Amer2 is expressed mainly in the dorsal neuroectoderm and neural tissues. Down-regulation of Amer2 by specific morpholino oligonucleotides altered neuroectodermal patterning, which could be rescued by expression of a dominant-negative mutant of Lef1 that interferes with β-catenin-dependent transcription. Our data characterize Amer2 for the first time as a negative regulator of Wnt signaling both in cell lines and in vivo and define Amer proteins as a novel family of Wnt pathway regulators.

An aggregon in conductin/axin2 regulates Wnt/β-catenin signaling and holds potential for cancer therapy - Bernkopf, Dominic; Brückner, Martina; Hadjihannas, Michel; Behrens, Jürgen (Nature Communications, 2019)
The paralogous scaffold proteins axin and conductin/axin2 are key factors in the negative regulation of the Wnt pathway transcription factor β-catenin, thereby representing interesting targets for signaling regulation. Polymerization of axin proteins is essential for their activity in suppressing Wnt/β-catenin signaling. Notably, conductin shows less polymerization and lower activity than axin. By domain swapping between axin and conductin we here identify an aggregation site in the conductin RGS domain which prevents conductin polymerization. Induction of conductin polymerization by point mutations of this aggregon results in enhanced inhibition of Wnt/β-catenin signaling. Importantly, we identify a short peptide which induces conductin polymerization via masking the aggregon, thereby enhancing β-catenin degradation, inhibiting β-catenin-dependent transcription and repressing growth of colorectal cancer cells. Our study reveals a mechanism for regulating signaling pathways via the polymerization status of scaffold proteins and suggests a strategy for targeted colorectal cancer therapy.
CRIS-Team Scopus Importer:2019-09-27

?-Arrestin Promotes Wnt-induced Low Density Lipoprotein Receptor-related Protein 6 (Lrp6) Phosphorylation via Increased Membrane Recruitment of Amer1 Protein - Kriz, Vitezslav; Pospichalova, Vendula; Masek, Jan; Kilander, Michaela Brita Christina; Slavik, Josef; Tanneberger, Kristina; Schulte, Gunnar; Machala, Miroslav; Kozubik, Alois; Behrens, Jürgen; Bryja, Vitezslav (Journal of Biological Chemistry, 2014)
?-Arrestin is a scaffold protein that regulates signal transduction by seven transmembrane-spanning receptors. Among other functions it is also critically required for Wnt/?-catenin signal transduction. In the present study we provide for the first time a mechanistic basis for the ?-arrestin function in Wnt/?-catenin signaling. We demonstrate that ?-arrestin is required for efficient Wnt3a-induced Lrp6 phosphorylation, a key event in downstream signaling. ?-Arrestin regulates Lrp6 phosphorylation via a novel interaction with phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P2)-binding protein Amer1/WTX/Fam123b. Amer1 has been shown very recently to bridge Wnt-induced and Dishevelled-associated PtdIns(4,5)P2 production to the phosphorylation of Lrp6. Using fluorescence recovery after photobleaching we show here that ?-arrestin is required for the Wnt3a-induced Amer1 membrane dynamics and downstream signaling. Finally, we show that ?-arrestin interacts with PtdIns kinases PI4KII? and PIP5KI?. Importantly, cells lacking ?-arrestin showed higher steady-state levels of the relevant PtdInsP and were unable to increase levels of these PtdInsP in response to Wnt3a. In summary, our data show that ?-arrestins regulate Wnt3a-induced Lrp6 phosphorylation by the regulation of the membrane dynamics of Amer1. We propose that ?-arrestins via their scaffolding function facilitate Amer1 interaction with PtdIns(4,5)P2, which is produced locally upon Wnt3a stimulation by ?-arrestin- and Dishevelled-associated kinases.
EVALuna2:10305

Breakdown of the Endothelial Barrier Function in Tumor Cell Transmigration - Mierke, Claudia; Paranhos Zitterbart, Daniel; Kollmannsberger, Philip; Raupach, Carina; Schlötzer-Schrehardt, Ursula; Goecke, Tamme W.; Behrens, Jürgen; Fabry, Ben (Biophysical Journal, 2007)
UnivIS-Import:2015-04-14:Pub.2007.nat.dphy.IAP.lpmt.breakd
Keywords: transendothelial migration; invasion; metastasis; endothelium; CXCR2; Gro-â; IL-8; cell mechanics

CD24 induces localization of beta1 integrin to lipid raft domains - Runz, Steffen; Mierke, Claudia; Joumaa, Safwan; Behrens, Jürgen; Fabry, Ben; Altevogt, Peter (Biochemical and Biophysical Research Communications, 2008)

Cell intrinsic Wnt/β-catenin signaling activation - Bernkopf, Dominic; Behrens, Jürgen (Aging-Us, 2018)
EVALuna2:34940

Chromatin-Remodeling-Factor ARID1B Represses Wnt/?-Catenin Signaling - Vasileiou, Georgia; Ekici, Arif Bülent; Urebe, Steffen; Zweier, Christiane; Hoyer, Juliane; Engels, Hartmut; Behrens, Jürgen; Reis, André; Hadjihannas, Michel (American Journal of Human Genetics, 2015)
The link of chromatin remodeling to both neurodevelopment and cancer has recently been highlighted by the identification of mutations affecting BAF chromatin-remodeling components, such as ARID1B, in individuals with intellectual disability and cancer. However, the underlying molecular mechanism(s) remains unknown. Here, we show that ARID1B is a repressor of Wnt/?-catenin signaling. Through whole-transcriptome analysis, we find that in individuals with intellectual disability and ARID1B loss-of-function mutations, Wnt/?-catenin target genes are upregulated. Using cellular models of low and high Wnt/?-catenin activity, we demonstrate that knockdown of ARID1B activates Wnt/?-catenin target genes and Wnt/?-catenin-dependent transcriptional reporters in a ?-catenin-dependent manner. Reciprocally, forced expression of ARID1B inhibits Wnt/?-catenin signaling downstream of the ?-catenin destruction complex. Both endogenous and exogenous ARID1B associate with ?-catenin and repress Wnt/?-catenin-mediated transcription through the BAF core subunit BRG1. Accordingly, mutations in ARID1B leading to partial or complete deletion of its BRG1-binding domain, as is often observed in intellectual disability and cancers, compromise association with ?-catenin, and the resultant ARID1B mutant proteins fail to suppress Wnt/?-catenin signaling. Finally, knockdown of ARID1B in mouse neuroblastoma cells leads to neurite outgrowth through ?-catenin. The data suggest that aberrations in chromatin-remodeling factors, such as ARID1B, might contribute to neurodevelopmental abnormalities and cancer through deregulation of developmental and oncogenic pathways, such as the Wnt/?-catenin signaling pathway.
EVALuna2:9258

Different Roles for the Axin Interactions with the SAMP versus the Second Twenty Amino Acid Repeat of Adenomatous Polyposis Coli - Schneikert, Jean; Ruppert, Jan Gustav; Behrens, Jürgen; Wenzel, Eva Maria (PLoS ONE, 2014)
Wnt signalling is prevented by the proteosomal degradation of ?-catenin, which occurs in a destruction complex containing adenomatous polyposis coli (APC), APC-like (APCL), Axin and Axin2. Truncating mutations of the APC gene result in the constitutive stabilisation of ?-catenin and the initiation of colon cancer, although tumour cells tolerate the expression of wild-type APCL. Using the colocalisation of overexpressed Axin, APC and APCL constructs as a readout of interaction, we found that Axin interacted with the second twenty amino acid repeat (20R2) of APC and APCL. This interaction involved a domain adjacent to the C-terminal DIX domain of Axin. We identified serine residues within the 20R2 of APCL that were involved in Axin colocalisation, the phosphorylation of truncated APCL and the down-regulation of ?-catenin. Our results indicated that Axin, but not Axin2, displaced APC, but not APCL, from the cytoskeleton and stimulated its incorporation into bright cytoplasmic dots that others have recognised as ?-catenin destruction complexes. The SAMP repeats in APC interact with the N-terminal RGS domain of Axin. Our data showed that a short domain containing the first SAMP repeat in truncated APC was required to stimulate Axin oligomerisation. This was independent of Axin colocalisation with 20R2. Our data also suggested that the RGS domain exerted an internal inhibitory constraint on Axin oligomerisation. Considering our data and those from others, we discuss a working model whereby ?-catenin phosphorylation involves Axin and the 20R2 of APC or APCL and further processing of phospho-?-catenin occurs upon the oligomerisation of Axin that is induced by binding the SAMP repeats in APC.
EVALuna2:10306

Expression and localization of axin 2 in colorectal carcinoma and its clinical implication - Schaal, Ute; Grenz, Sandra; Merkel, Susanne; Rau, Tilman; Hadjihannas, Michel; Kremmer, Elisabeth; Chudasama, Priya; Croner, Roland S.; Behrens, Jürgen; Stürzl, Michael; Naschberger, Elisabeth (International Journal of Colorectal Disease, 2013)
Purpose: Aberrant activation of the Wnt/β-catenin pathway plays a major role in the development of colorectal carcinoma (CRC). Axin 2 is a key protein of this pathway and is upregulated in CRC. Here, we investigated RNA- and protein expression of axin 2 in CRC tissues at the single cell level. Moreover, the association of axin 2 with prognosis and survival was investigated in a large cohort of CRC patients (n = 280). Methods: Localization and expression of axin 2 and β-catenin was investigated using in situ hybridization and immunohistochemical staining. The quantitative expression levels of axin 2 were determined using RT-qPCR. The association of axin 2 expression with prognosis and survival of the patients was determined by statistical analysis (logrank test, Kaplan-Meier). Results: Our results confirmed the upregulation of axin 2 in CRC and showed that it is broadly expressed in the cytoplasm of the tumor epithelial cells both, in the tumor center and at the invasion front. Axin 2 was rarely expressed by tumor stromal cells and only weakly by normal colonic epithelial cells. Staining of β-catenin and axin 2 in consecutive CRC tissue sections revealed that nuclear translocation of β-catenin in the tumor front was not associated with changes in the cytoplasmic localization of axin 2. Axin 2 did not show any association with proven prognostic factors or survival of the CRC patients. Conclusion: The generally increased expression of axin 2 in all tumor stages as compared to normal tissue suggests an initiating pathogenic function in the development of CRC. © 2013 Springer-Verlag Berlin Heidelberg.
Created from Fastlane, Scopus look-up
Keywords: β-Catenin; Axin 2; Colorectal carcinoma; Wnt/β-catenin signaling

Feedback regulation of mitochondrial homeostasis via Wnt/β-catenin signaling - Bernkopf, Dominic; Behrens, Jürgen (Molecular & Cellular Oncology, 2018)
Cellular abundance of mitochondria is dynamically regulated. We could recently show that dysfunctional mitochondria release the phosphatase PGAM family member 5 (PGAM5) into the cytosol, where it interacts with the Wnt signaling-component AXIN1 and dephosphorylates AXIN1-bound β-catenin (CTNNB1) thereby activating Wnt/β-catenin signaling. Because Wnt/β-catenin signaling induces mitochondrial biogenesis dysfunctional mitochondria trigger their own replacement by releasing PGAM5.
EVALuna2:34941

Genetic and molecular insights into genotype-phenotype relationships in osteopathia striata with cranial sclerosis (OSCS) through the analysis of novel mouse Wtx mutant alleles - Comai, Glenda; Boutet, Agnès; Tanneberger, Kristina; Massa, Filippo; Rocha, Ana Sofia; Charlet, Aurelie; Panzolini, Clara; Jian Motamedi, Fariba; Brommage, Robert; Hans, Wolfgang; Funck-Brentano, Thomas; Hrabe de Angelis, Martin; et al. (Journal of Bone and Mineral Research, 2018)
The X-linked WTX/AMER1 protein forms an important component of the ?-catenin destruction complex that can both enhance and suppress canonical ?-catenin signalling. Somatic mutations in WTX/AMER1 have been found in a proportion of the pediatric kidney cancer Wilms' tumour. By contrast, germline mutations cause the severe sclerosing bone dysplasia osteopathia striata congenita with cranial sclerosis (OSCS), a condition usually associated with fetal or perinatal lethality in male patients. Here we addressed the developmental and molecular function of WTX by generating two novel mouse alleles. We show that in addition to the previously reported skeletal abnormalities, loss of Wtx causes severe midline fusion defects including cleft palate and ectopic synostosis at the base of the skull. By contrast, deletion of the C-terminal part of the protein results in only mild developmental abnormalities permitting survival beyond birth. Adult analysis however revealed skeletal defects including changed skull morphology and an increased whole body bone density, resembling a subgroup of male patients carrying a milder, survivable phenotype. Molecular analysis in vitro demonstrated that while ?-catenin fails to co-immunoprecipitate with the truncated protein, partial recruitment appears to be achieved in an indirect manner using AXIN/AXIN2 as a molecular bridge. Taken together our analysis provides a novel model for WTX-caused bone diseases and explains on the molecular level how truncation mutations in this gene may retain some of WTX-protein functions. This article is protected by copyright. All rights reserved.
EVALuna2:10311

GSK3ss-Dependent Dysregulation of Neurodevelopment in SPG11-Patient Induced Pluripotent Stem Cell Model - Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Pérez-Brangulí, Francesc; Börstler, Tom; Anneser, Lukas; Minakaki, Georgia; Wend, Holger; Hampl, Martin; Leone, Marina; Brückner, Martina; et al. (Annals of Neurology, 2016)
Objective: Mutations in the spastic paraplegia gene 11 (SPG11), encoding spatacsin, cause the most frequent form of autosomal-recessive complex hereditary spastic paraplegia (HSP) and juvenile-onset amyotrophic lateral sclerosis (ALS5). When SPG11 is mutated, patients frequently present with spastic paraparesis, a thin corpus callosum, and cognitive impairment. We previously delineated a neurodegenerative phenotype in neurons of these patients. In the current study, we recapitulated early developmental phenotypes of SPG11 and outlined their cellular and molecular mechanisms in patient-specific induced pluripotent stem cell (iPSC)-derived cortical neural progenitor cells (NPCs).Methods: We generated and characterized iPSC-derived NPCs and neurons from 3 SPG11 patients and 2 age-matched controls.Results: Gene expression profiling of SPG11-NPCs revealed widespread transcriptional alterations in neurodevelopmental pathways. These include changes in cell-cycle, neurogenesis, cortical development pathways, in addition to autophagic deficits. More important, the GSK3ss-signaling pathway was found to be dysregulated in SPG11-NPCs. Impaired proliferation of SPG11-NPCs resulted in a significant diminution in the number of neural cells. The decrease in mitotically active SPG11-NPCs was rescued by GSK3 modulation.Interpretation: This iPSC-derived NPC model provides the first evidence for an early neurodevelopmental phenotype in SPG11, with GSK3ss as a potential novel target to reverse the disease phenotype.

Gαi2-induced conductin/axin2 condensates inhibit Wnt/β-catenin signaling and suppress cancer growth - Miete, Cezanne; Solis, Gonzalo P.; Koval, Alexey; Brückner, Martina; Katanaev, Vladimir L.; Behrens, Jürgen; Bernkopf, Dominic (Nature Communications, 2022)
Conductin/axin2 is a scaffold protein negatively regulating the pro-proliferative Wnt/β-catenin signaling pathway. Accumulation of scaffold proteins in condensates frequently increases their activity, but whether condensation contributes to Wnt pathway inhibition by conductin remains unclear. Here, we show that the Gαi2 subunit of trimeric G-proteins induces conductin condensation by targeting a polymerization-inhibiting aggregon in its RGS domain, thereby promoting conductin-mediated β-catenin degradation. Consistently, transient Gαi2 expression inhibited, whereas knockdown activated Wnt signaling via conductin. Colorectal cancers appear to evade Gαi2-induced Wnt pathway suppression by decreased Gαi2 expression and inactivating mutations, associated with shorter patient survival. Notably, the Gαi2-activating drug guanabenz inhibited Wnt signaling via conductin, consequently reducing colorectal cancer growth in vitro and in mouse models. In summary, we demonstrate Wnt pathway inhibition via Gαi2-triggered conductin condensation, suggesting a tumor suppressor function for Gαi2 in colorectal cancer, and pointing to the FDA-approved drug guanabenz for targeted cancer therapy.
CRIS-Team Scopus Importer:2022-02-11

Hypoxia regulates the sperm associated antigen 4 (SPAG4) via HIF, which is expressed in renal clear cell carcinoma and promotes migration and invasion in vitro - Knaup, Karl; Monti, Juliana; Hackenbeck, Thomas; Jobst-Schwan, Tilman; Klanke, Bernd; Schietke, Ruth Elisabeth; Wacker, Ingrid; Behrens, Jürgen; Amann, Kerstin Ute; Eckardt, Kai-Uwe; Warnecke, Christina; Wiesener, Michael (Molecular Carcinogenesis, 2014)
Hypoxia leads to the upregulation of a variety of genes mediated largely via the hypoxia inducible transcription factor (HIF). Prominent HIF-regulated target genes such as the vascular endothelial growth factor (VEGF), the glucose transporter 1 (Glut-1), or erythropoietin (EPO) help to assure survival of cells and organisms in a low oxygenated environment. Here, we are the first to report the hypoxic regulation of the sperm associated antigen 4 (SPAG4). SPAG4 is a member of the cancer testis (CT) gene family and to date little is known about its physiological function or its involvement in tumor biology. A number of CT family candidate genes are therefore currently being investigated as potential cancer markers, due to their predominant testicular expression pattern. We analyzed RNA and protein expression by RNAse protection assay, immunoflurescent as well as immunohistological stainings. To evaluate the influence of SPAG4 on migration and invasion capabilities, siRNA knockdown as well as transient overexpression was performed prior to scratch or invasion assay analysis. The hypoxic regulation of SPAG4 is clearly mediated in a HIF-1 and VHL dependent manner. We furthermore show upregulation of SPAG4 expression in human renal clear cell carcinoma (RCC) and co-localization within the nucleolus in physiological human testis tissue. SPAG4 knockdown reduces the invasion capability of RCC cells in vitro and overexpression leads to enhancement of tumor cell migration. Together, SPAG4 could possibly play a role in the invasion capability and growth of renal tumors and could represent an interesting target for clinical intervention. © 2013 Wiley Periodicals, In
EVALuna2:3620

IFN-γ-response mediator GBP-1 represses human cell proliferation by inhibiting the Hippo signaling transcription factor TEAD - Unterer, Bea; Wiesmann, Veit; Gunasekaran, Mekala; Sticht, Heinrich; Tenkerian, Clara; Behrens, Jürgen; Leone, Marina; Engel, Felix; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Wittenberg, Thomas; Stürzl, Michael (Biochemical Journal, 2018)
Interferon-gamma (IFN-γ) is a pleiotropic cytokine that exerts important functions in inflammation, infectious diseases, and cancer. The large GTPase human guanylate-binding protein 1 (GBP-1) is among the most strongly IFN-γ-induced cellular proteins. Previously, it has been shown that GBP-1 mediates manifold cellular responses to IFN-γ including the inhibition of proliferation, spreading, migration, and invasion and through this exerts anti-tumorigenic activity. However, the mechanisms of GBP-1 anti-tumorigenic activities remain poorly understood. Here, we elucidated the molecular mechanism of the human GBP-1-mediated suppression of proliferation by demonstrating for the first time a cross-talk between the anti-tumorigenic IFN-γ and Hippo pathways. The α9-helix of GBP-1 was found to be sufficient to inhibit proliferation. Protein-binding and molecular modeling studies revealed that the α9-helix binds to the DNA-binding domain of the Hippo signaling transcription factor TEA domain protein (TEAD) mediated by the 376VDHLFQK382 sequence at the N-terminus of the GBP-1-α9-helix. Mutation of this sequence resulted in abrogation of both TEAD interaction and suppression of proliferation. Further on, the interaction caused inhibition of TEAD transcriptional activity associated with the down-regulation of TEAD-target genes. In agreement with these results, IFN-γ treatment of the cells also impaired TEAD activity, and this effect was abrogated by siRNA-mediated inhibition of GBP-1 expression. Altogether, this demonstrated that the α9-helix is the proliferation inhibitory domain of GBP-1, which acts independent of the GTPase activity through the inhibition of the Hippo transcription factor TEAD in mediating the anti-proliferative cell response to IFN-γ.
EVALuna2:34818

Liprin-α4 is a new hypoxia-inducible target gene required for maintenance of cell-cell contacts - Mattauch, Sandra; Sachs, Martin; Behrens, Jürgen (Experimental Cell Research, 2010)
Liprin-α1 to liprin-α4 constitute a family of cytoplasmic proteins, which have been found in various multiprotein complexes. For liprin-α1 roles in synapse formation and cell spreading were described but other liprin family members are not well characterized. We show here that liprin-α4 is upregulated in human clear cell renal cell carcinomas (RCC) as compared to normal kidney tissue. Liprin-α4 expression is downregulated by the von Hippel-Lindau tumor suppressor (VHL) and upregulated by hypoxia in RCC cell lines. The liprin-α4 gene promoter is directly activated by binding of the hypoxia-inducible factor 1α (HIF-1α) to HRE consensus binding sites as shown by reporter assays and chromatin immunoprecipitations. RNAi mediated knockdown of liprin-α4 leads to reduced E-cadherin and Β-catenin levels at cell junctions and to dissociation of epithelial cell contacts. Our data describe for the first time liprin-α4 as a hypoxia-induced gene potentially involved in cell-cell adhesion. © 2010 Elsevier Inc.
Created from Fastlane, Scopus look-up
Keywords: Cell-cell contacts; E-cadherin; HIF; Liprin; RCC; VHL

Molecular signature for lymphatic metastasis in colorectal carcinomas. - Croner, Roland S.; Förtsch, Thomas; Brueckl, Wolfgang M.; Roedel, Franz; Roedel, Claus; Papadopoulos, Thomas; Brabletz, Thomas; Kirchner, Thomas; Sachs, Martin; Behrens, Jürgen; Klein-Hitpass, Ludger; Stürzl, Michael; et al. (Annals of Surgery, 2008)
Fifty differently expressed genes between stage UICC I, II versus III CRC were identified respecting the selection criteria by allowing for multiple testing. The data validation by the independent clinical study confirmed our results. In comparison to MC, the genes were over- or underexpressed. They belong to various functional groups such as cellular adhesion, transporters, signaling, metabolism, protein synthesis, gene control, and immune system. Forty tumor samples of stage UICC I, II CRC, 40 samples of stage III CRC, and 25 biopsies of healthy mucosa (MC) were shock frozen in liquid nitrogen and underwent cryotomy after manual dissection for tumor tissue or MC enrichment. Isolated RNA was hybridized to GeneChips (HG-U133A, Affymetrix). Preprocessing of the microarray results was done by the robust multichip average method, and differentially expressed genes were selected by the maximum Wilcoxon statistic over 22,215 probe sets. The results were validated at an independent clinical study. Our large patient cohort and the data validation on an independent study identified 50 differentially expressed genes between CRC of different histopathologic stages. These findings indicate that molecular staging of CRC may be possible, which could help to guide individual CRC treatment before surgery. TNM-staging of colorectal carcinomas (CRC) relies on the histopathologic workup of the surgically removed specimen. If valid preoperative staging methods existed, patients could be selected for adequate individual therapy before surgery. Microarray techniques provide a promising tool to identify stage-specific molecular signatures on primary tumor biopsies. RESULTS MATERIAL AND METHODS CONCLUSION PURPOSE

Negative-feedback regulation of the Wnt pathway by conductin/axin2 involves insensitivity to upstream signalling - Bernkopf, Dominic; Hadjihannas, Michel; Behrens, Jürgen (Journal of Cell Science, 2015)
Axin and conductin (also known as axin2) are structurally related inhibitors of Wnt/?-catenin signalling that promote degradation of ?-catenin. Whereas axin is constitutively expressed, conductin is a Wnt target gene implicated in Wnt negative-feedback regulation. Here, we show that axin and conductin differ in their functional interaction with the upstream Wnt pathway component Dvl. Conductin shows reduced binding to Dvl2 compared to axin, and degradation of ?-catenin by conductin is only poorly blocked by Dvl2. We propose that insensitivity to Dvl is an important feature of the role of conductin as a negative-feedback regulator of Wnt signalling.
EVALuna2:10308

Pgam5 released from damaged mitochondria induces mitochondrial biogenesis via Wnt signaling - Bernkopf, Dominic; Jalal, Kowcee; Brückner, Martina; Knaup, Karl; Gentzel, Marc; Schambony, Alexandra; Behrens, Jürgen (The Journal of Cell Biology, 2018)
Mitochondrial abundance is dynamically regulated and was previously shown to be increased by Wnt/β-catenin signaling. Pgam5 is a mitochondrial phosphatase which is cleaved by the rhomboid protease presenilin-associated rhomboid-like protein (PARL) and released from membranes after mitochondrial stress. In this study, we show that Pgam5 interacts with the Wnt pathway component axin in the cytosol, blocks axin-mediated β-catenin degradation, and increases β-catenin levels and β-catenin-dependent transcription. Pgam5 stabilized β-catenin by inducing its dephosphorylation in an axin-dependent manner. Mitochondrial stress triggered by carbonyl cyanide m-chlorophenyl hydrazone (CCCP) treatment led to cytosolic release of endogenous Pgam5 and subsequent dephosphorylation of β-catenin, which was strongly diminished in Pgam5 and PARL knockout cells. Similarly, hypoxic stress generated cytosolic Pgam5 and led to stabilization of β-catenin, which was abolished by Pgam5 knockout. Cells stably expressing cytosolic Pgam5 exhibit elevated β-catenin levels and increased mitochondrial numbers. Our study reveals a novel mechanism by which damaged mitochondria might induce replenishment of the mitochondrial pool by cell-intrinsic activation of Wnt signaling via the Pgam5-β-catenin axis.
EVALuna2:34942

Structural and functional characterization of the Wnt inhibitor APC membrane recruitment 1 (Amer1). - Tanneberger, Kristina; Pfister, Astrid; Kriz, Vitezslav; Bryja, Vitezslav; Schambony, Alexandra; Behrens, Jürgen (Journal of Biological Chemistry, 2011)
Amer1/WTX binds to the tumor suppressor adenomatous polyposis coli and acts as an inhibitor of Wnt signaling by inducing β-catenin degradation. We show here that Amer1 directly interacts with the armadillo repeats of β-catenin via a domain consisting of repeated arginine-glutamic acid-alanine (REA) motifs, and that Amer1 assembles the β-catenin destruction complex at the plasma membrane by recruiting β-catenin, adenomatous polyposis coli, and Axin/Conductin. Deletion or specific mutations of the membrane binding domain of Amer1 abolish its membrane localization and abrogate negative control of Wnt signaling, which can be restored by artificial targeting of Amer1 to the plasma membrane. In line, a natural splice variant of Amer1 lacking the plasma membrane localization domain is deficient for Wnt inhibition. Knockdown of Amer1 leads to the activation of Wnt target genes, preferentially in dense compared with sparse cell cultures, suggesting that Amer1 function is regulated by cell contacts. Amer1 stabilizes Axin and counteracts Wnt-induced degradation of Axin, which requires membrane localization of Amer1. The data suggest that Amer1 exerts its negative regulatory role in Wnt signaling by acting as a scaffold protein for the β-catenin destruction complex and promoting stabilization of Axin at the plasma membrane.

Sulforaphane inhibits growth and blocks Wnt/β-catenin signaling of colorectal cancer cells - Bernkopf, Dominic; Daum, Gabriele; Brückner, Martina; Behrens, Jürgen (Oncotarget, 2018)
The naturally occurring isothiocyanate sulforaphane (SFN) from cruciferous vegetables is associated with growth inhibition of various cancer types, including colorectal cancer. Colorectal cancer is most frequently driven by hyperactive Wnt/β-catenin signaling. Here, we show that SFN treatment reduced growth of three unrelated colorectal cancer cell lines (SW480, DLD1 and HCT116) via induction of cell death and inhibition of proliferation. Importantly, SFN inhibits Wnt/β-catenin signaling in colorectal cancer cells as shown by inhibition of β-catenin-dependent luciferase reporters and repression of β-catenin target genes (AXIN2, LGR5). SFN inhibits Wnt signaling downstream of β-catenin degradation and induces the formation of nuclear β-catenin structures associated with closed chromatin. Co-expression of the transcription factors LEF1 or TCF4 prevented formation of these structures and rescued inhibition of Wnt/β-catenin signaling by SFN. Our findings provide a molecular basis explaining SFN effects in colorectal cancer cells and underline its potential for prevention and therapy of colorectal cancer.
EVALuna2:34943

The lysyl oxidases LOX and LOXL2 are necessary and sufficient to repress E-cadherin in Hypoxia: Insights into cellular transformation processes mediated by HIF-1 - Schietke, Ruth; Warnecke, Christina; Wacker, Ingrid; Schödel, Johannes; Mole, David R.; Campean, Valentina; Amann, Kerstin Ute; Goppelt-Strübe, Margarete; Behrens, Jürgen; Eckardt, Kai-Uwe; Wiesener, Michael Sean (Journal of Biological Chemistry, 2010)
Hypoxia has been shown to promote tumor metastasis and lead to therapy resistance. Recent work has demonstrated that hypoxia represses E-cadherin expression, a hallmark of epithelial to mesenchymal transition, which is believed to amplify tumor aggressiveness. The molecular mechanism of E-cadherin repression is unknown, yet lysyl oxidases have been implicated to be involved. Gene expression of lysyl oxidase (LOX) and the related LOX-like 2 (LOXL2) is strongly induced by hypoxia. In addition to the previously demonstrated LOX, we characterize LOXL2 as a direct transcriptional target of HIF-1. We demonstrate that activation of lysyl oxidases is required and sufficient for hypoxic repression of E-cadherin, which mediates cellular transformation and takes effect in cellular invasion assays. Our data support a molecular pathway from hypoxia to cellular transformation. It includes up-regulation of HIF and subsequent transcriptional induction of LOX and LOXL2, which repress E-cadherin and induce epithelial to mesenchymal transition. Lysyl oxidases could be an attractive molecular target for cancers of epithelial origin, in particular because they are partly extracellular. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2024-05-13

The phosphatase Pgam5 antagonizes Wnt/β-catenin signaling in embryonic anterior-posterior axis patterning - Rauschenberger, Verena; Bernkopf, Dominic; Krenn, Sabrina; Jalal, Kowcee; Heller, Jens; Behrens, Jürgen; Gentzel, Marc; Schambony, Alexandra (Development, 2017)
Keywords: Anteriorposterior patterning; Dvl2; Pgam5; Phosphatase; Wnt; Xenopus

Wnt/?-catenin signaling via Axin2 is required for myogenesis and, together with YAP/Taz and Tead1, active in IIa/IIx muscle fibers - Huraskin, Danyil; Eiber, Nane; Reichel, Martin; Zidek, Laura M.; Kravic, Bojana; Bernkopf, Dominic; von Maltzahn, Julia; Behrens, Jürgen; Hashemolhosseini, Said (Development, 2016)
Canonical Wnt/?-catenin signaling plays an important role in myogenic differentiation, but its physiological role in muscle fibers remains elusive. Here, we studied activation of Wnt/?-catenin signaling in adult muscle fibers and muscle stem cells in an Axin2 reporter mouse. Axin2 is a negative regulator and a target of Wnt/?-catenin signaling. In adult muscle fibers, Wnt/?-catenin signaling is only detectable in a subset of fast fibers that have a significantly smaller diameter than other fast fibers. In the same fibers, immunofluorescence staining for YAP/Taz and Tead1 was detected. Wnt/?-catenin signaling was absent in quiescent and activated satellite cells. Upon injury, Wnt/?-catenin signaling was detected in muscle fibers with centrally located nuclei. During differentiation of myoblasts expression of Axin2, but not of Axin1, increased together with Tead1 target gene expression. Furthermore, absence of Axin1 and Axin2 interfered with myoblast proliferation and myotube formation, respectively. Treatment with the canonical Wnt3a ligand also inhibited myotube formation. Wnt3a activated TOPflash and Tead1 reporter activity, whereas neither reporter was activated in the presence of Dkk1, an inhibitor of canonical Wnt signaling. We propose that Axin2-dependent Wnt/?-catenin signaling is involved in myotube formation and, together with YAP/Taz/Tead1, associated with reduced muscle fiber diameter of a subset of fast fibers.
EVALuna2:4993